2020
DOI: 10.5194/egusphere-egu2020-8469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensing small-scale structures in the troposphere with tomographic principles (IAG working group)

Abstract: <p>Within the International Association of Geodesy (IAG), a new working group was formed with the intention to bring together researchers and professionals working on tomography-based concepts for sensing the neutral atmosphere with space-geodetic techniques. Hereby the focus lies on Global Navigation Satellite Systems (GNSS) but also on complementary observation techniques, like Interferometric Synthetic Aperature Radar (InSAR) or microwave radiometers, sensitive to the water vapor distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Tratando adequadamente as limitações, a tomografia-GNSS é uma ferramenta promissora na detecção da alta variabilidade espaço-temporal do vapor d'água. Diferentes trabalhos atuais apresentam as melhorias quanto à técnica: Bender et al (2011), Brenot et al (2020), Zhang et al (2020) e Moeller et al (2020). No Brasil, tais estudos ainda não foram desenvolvidos.…”
Section: Tomografia-gnss Do Vapor D'águaunclassified
See 1 more Smart Citation
“…Tratando adequadamente as limitações, a tomografia-GNSS é uma ferramenta promissora na detecção da alta variabilidade espaço-temporal do vapor d'água. Diferentes trabalhos atuais apresentam as melhorias quanto à técnica: Bender et al (2011), Brenot et al (2020), Zhang et al (2020) e Moeller et al (2020). No Brasil, tais estudos ainda não foram desenvolvidos.…”
Section: Tomografia-gnss Do Vapor D'águaunclassified
“…Um estudo recente propõe o uso de receptores GNSS para prever (com antecedência de 30 minutos) eventos extremos de precipitação (>35mm) (SAPUCCI et al, 2019) e há projetos visando explorar dados do COSMIC-2 (constelação de satélites equatoriais dedicados para RO-GNSS) para prever eventos extremos de precipitação (BANOS et al, 2018). Um desenvolvimento em paralelo vem sendo a tomografia do vapor d'água (BRENOT et al, 2020), com potencial de melhor detalhar a distribuição temporal e espacial dessa variável (MOELLER et al, 2020). É consenso que previsão de tempo em condições atmosféricas extremas (severas) é desafiadora e encontra-se na fronteira do conhecimento humano, no qual a sinergia em diferentes áreas do conhecimento é um dos ingredientes mais importantes para se obter o sucesso.…”
Section: Introductionunclassified
“…Hence, for ground-based GNSS tomography, the transmitter-receiver geometry does not favor the high vertical resolution and leads to solution instability (Trzcina and Rohm 2019;Liu et al 2019). Conversely, Moeller et al (2019) has shown that a tomographic "peeling" approach with space-based observations can significantly increase the vertical resolution if applied to radio occultation measurements. The scanning rays, in our solution, will come from ground-and space-based GNSS observations.…”
Section: Introductionmentioning
confidence: 99%